1996
DOI: 10.1002/chem.19960021215
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Control in the Pictet–Spengler Reaction by Means of N‐Protected Amino Acids as Chiral Auxiliary Groups

Abstract: Aromatic and aliphatic Schiff bases of tryptamine react with Fmoc-or phthaloyl-protected amino acid chlorides to form N-acyliminium intermediates, which, in tions to give tetrahydro-fl-carbolines with diastereomeric ratios of up to 99: 1. The chiral reduction. To rationalize the observed stereoselectivity a transition-state model is proposed in which the titanium atom coordinates both the carbonyl group of the N-acyliminium ion and the amino acid protecting group. the presence of titanium alkoxides at room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…This salt was collected by filtration and then neutralized to provide pure 1 a in 87 % yield and with 84 % ee ( Table 2). Comparison of the sign of the specific rotation of the product with literature data [3] indicated that (S)-1 a was formed as the major enantiomer when (R)-9 d was used as the catalyst.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This salt was collected by filtration and then neutralized to provide pure 1 a in 87 % yield and with 84 % ee ( Table 2). Comparison of the sign of the specific rotation of the product with literature data [3] indicated that (S)-1 a was formed as the major enantiomer when (R)-9 d was used as the catalyst.…”
mentioning
confidence: 94%
“…It is possible to start with an enantiomerically pure chiral tryptamine, such as a tryptophan derivative, or aldehyde; alternatively, the use of a chiral auxiliary attached to the nitrogen atom has been successful. Two remarkable examples are the cyclization of the N-acyliminium ion 2, in which an a-N,Nphthaloylamino acid is used as a chiral auxiliary, [3] and the cyclization of the N-sulfinyliminium ion 3, with the use of menthyl p-toluenesulfinate as a chiral reagent.[4] The former procedure proceeds with very high diastereoselectivity, but the chiral auxiliary can be removed only under relatively harsh reductive conditions. Lower selectivity is observed with the second method, but the diastereomers are readily separable, and the sulfinyl auxiliary can be cleaved easily by mild hydrolysis.…”
mentioning
confidence: 99%
“…The reaction conditions were suitable for both aliphatic and aromatic aldehydes. However, removal of the auxiliary was obtained with LiAlH4 in only 66% yield (Scheme 16) [60]. The obtained carboline was R-configured that is enantiomeric with that obtained in the previous examples.…”
Section: Chiral Auxiliariesmentioning
confidence: 82%
“…The stereoselectivity was influenced by condensation with chiral carbonyl derivatives [6] or by the use of internal [7] or external devices [8]. 4.…”
mentioning
confidence: 99%